Somatic hypermutation of an immunoglobulin mu heavy chain transgene (The Rockefeller University Press, 1993)
We have analyzed somatic hypermutation of an immunoglobulin (Ig) heavy chain transgene. Hybridomas expressing the transgene were produced from immunized transgenic mice and transgene copies were sequenced to assay for mutation. In two IgM-producing hybridomas, as well as in several IgG-producing hybridomas, mutations were found in the VDJ region of the transgene. In the IgM-producing hybridomas, both mutated and unmutated transgene copies were present and expressed as mRNA. Several mutated transgene copies were present in a single cell and these showed different patterns of mutation. Two IgG-producing hybridomas isolated from a single animal also showed a hierarchical pattern of mutation indicating that transgene mutations can accumulate during B cell proliferation, similar to the mutational process for endogenous antibody genes. Among hybridomas that expressed both IgG and IgM molecules derived from the transgene, the isotype-switched gamma transgene copy exhibited a higher level of mutation than the mu transgene copies. Our results indicate that the 15-kb ARSmu transgene contains all the sequence information required to target the Ig- specific hypermutational machinery, and raise the possibility that sequences associated with the endogenous CH locus might enhance somatic mutation.